Hormone Consumption among Mak Nyahs in Kuantan Town: A Preliminary Survey - S, Draman; S, Maliya; A, Farhan; S, Syazwan; A, Nur ‘Atikah; Abd Aziz, KH (IIUM Medical Journal Malaysia, 2018)
Introduction: Mak nyahs (male-to-female transgenders) often consume feminizing hormones to achieve and maintain the female physical appearance. They do it without professional prescription/advise, and often take excessive doses. This renders them at risk of developing complications of hormone consumption. This paper provides some quantitative data on hormone consumption among mak nyahs in Kuantan, Pahang, in Malaysia. Materials and Methods: A cross-sectional study was carried out from July to August in 2015 among 35 mak nyahs. Convenience sampling was used. Participants who gave consent answered an interview-guided questionnaire which documents socio-demographic profile, hormone usage, and morbidities as a result of hormone consumption. Data was analysed using SPSS, Version 16.0. (version 16). Results: Majority of the subjects were Malays (91.4%) and Muslims (97.1%), their median (IQR) age being 31 (±17) years, more than half (57.1%) were between 20 to 40 years old. Most (80.0%) of them are sex workers. Oral hormone was most commonly used (88.6%), while more than half (67.7%) of them added hormone injections. Almost all subjects purchased hormones over the counter from local pharmacies (94.2%). However, many received information on hormone from non-professional sources. Possible adverse effects of hormones reported among subjects were hypertension, ischemic heart disease, diabetes mellitus, and venous thrombo-embolism. Conclusion: Hormone consumption was very common among the subjects in this study, and may be associated with certain medical problems. Medical personnel must pay more attention in educating the mak nyahs on adverse effects of hormones consumption. Mak nyahs should also be screened for complications every time they seek medical attention.